Market structure and coherence of international cooperation: the case of the dairy sector in Malawi - Cesar Revoredo-Giha; Alan Renwick (Agricultural and Food Economics, 2016)
A supply chain in disarray can be identified as a barrier not only to growth for the agricultural sector but also to achieving food security in a country because it may lead to either a deficiency in food production and/or too high prices. Using the dairy sector of Malawi as an example, the purpose of this paper is to discuss the coherence between market structure and the development strategy pursued by international donors. Within Malawi the dairy sector may be characterised as a segmented market: with both formal and informal milk markets, with smallholder producers serving both markets. The formal market includes few processing firms operating with idle capacity and selling dairy products to an affluent segment of the urban population, whilst the informal market comprises the sale of unprocessed milk products to the less affluent urban population and also rural areas. In this context, cooperative international action, conducted through agencies from a range of countries, is targeted at improving the efficiency of the formal supply chain and also the creation of local supply chains that sell processed products directly to poor consumers. The paper discusses reasons why these two cooperation strategies, given the structure of the sector, may potentially conflict with each other, the need to address the degree of market imperfection of the formal sector and the desirability of ex-ante coordination of plans amongst donors.
Keywords: 330; Malawi dairy supply chain; Development economics; Industrial organisation